Find all School-related info fast with the new School-Specific MBA Forum

 It is currently 17 Apr 2015, 20:54

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# Is m =1? 1)m^3=m 2)m^4=1

Author Message
TAGS:
Director
Joined: 09 Oct 2005
Posts: 722
Followers: 3

Kudos [?]: 12 [0], given: 0

Is m =1? 1)m^3=m 2)m^4=1 [#permalink]  20 Jun 2006, 06:52
00:00

Difficulty:

(N/A)

Question Stats:

0% (00:00) correct 0% (00:00) wrong based on 1 sessions
Is m =1?
1)m^3=m
2)m^4=1
_________________

IE IMBA 2010

Director
Joined: 07 Jun 2006
Posts: 513
Followers: 10

Kudos [?]: 89 [0], given: 0

Re: DS number prop [#permalink]  20 Jun 2006, 06:58
Yurik79 wrote:
Is m =1?
1)m^3=m
2)m^4=1

(2) INSUFF because, for e.g. -1^4 = 1^4 =1
(1) m^3 = m*m^2 = m, so again -1 or 1 are probable, INSUFF

combining (1) and (2) m* (m ^3) = 1 => m* (m) = 1, again, -1 or 1 are possible.

(E)
_________________

http://onwardtomba.blogspot.com - MBA, GMAT, INSEAD - the journey.
My 7 GMAT Quant Strategies/Trap
My GMAT Debrief

VP
Joined: 02 Jun 2006
Posts: 1267
Followers: 2

Kudos [?]: 42 [0], given: 0

Is m = 1?
1)m^3=m
if m = 1 => yes,
if m = 13^(1/3) then m^3 = m => no,

=> Not sufficient

2)m^4=1
if m = 1 => yes,
if m = 7 => no, => Not sufficient

(1) & (2):
m^4 = m^3
or m^3(m-1) = 0

or m = 0 or m =1 Still not sufficient.

Manager
Joined: 09 Apr 2006
Posts: 173
Location: Somewhere in Wisconsin!
Followers: 1

Kudos [?]: 2 [0], given: 0

Ans is E as m = +/-1 cannot be eliminated even after combining I and II.
_________________

Thanks,
Zooroopa

Director
Joined: 28 Dec 2005
Posts: 758
Followers: 1

Kudos [?]: 8 [0], given: 0

Here's how I solved it:

1: m3 = m
=> m3 - m = 0
=>m(m-1)(m+1)=0

m = 0, 1, -1

So 1 is insufficient.

2: m4=1
=>m = 1, -1

So 2 is sufficient

Combining 1 and 2, m is 1,-1, so still sufficient, therefore E.
Similar topics Replies Last post
Similar
Topics:
3 If m > 1 and n = 2^(m −1), then 4^m = 10 03 Dec 2014, 07:28
1 If m^(-1) = -1/3 then m^(-2) is equal to 2 20 Dec 2012, 06:23
7 M04 #1 26 22 Sep 2008, 18:48
Is m =1? 1)m^3=m 2)m^4=1 2 12 Aug 2007, 13:46
1/ , then m=? TIA 6 18 Apr 2007, 21:55
Display posts from previous: Sort by